Targeting compression energy in batch process - Gaurav Shukla (Elsevier, 2021)
Batch process is widely used in food, agrochemical, and pharmaceutical industries to generate high-priced fine chemicals. Resource conservation problems such as water minimization, energy minimization and hydrogen management has been extensively explored using mathematical optimization and graphical methods for the continuous process in the last few decades. On the other hand, resource conservation in batch process is comparatively less focussed. Batch processes require pumping, piping, and capital investment for the transfer of flow within different time intervals in addition to the intra-pressure level requirements. Compression procedures involve huge amounts of energy that are typically supplied by the compressors. A systematic method is needed for calculating minimum compression energy while satisfying the demand in batch gas allocation network (GAN). In this paper, a novel graphical method based on Pinch Analysis for minimization of compression energy in batch GAN while satisfying minimum resource requirement is presented. This methodology applies to any fixed-scheduled batch GAN. Applications of the proposed methodology are illustrated via two examples. In one of the illustrative examples, reduction of 8% in resource requirement and almost 5% in compression energy is observed when compared to the case where integration between intervals is not considered. This demonstrates that the proposed methodology has significant energy as well as resource-saving potential.